2017
DOI: 10.5194/acp-2017-1020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the evolution of physical properties and mixing state of black carbon particles: from near a major highway to the broader urban plume in Los Angeles

Abstract: Abstract. Black carbon particles can have deleterious human health consequences and impact regional and global climate. 10Uncertainties remain in part due to incomplete knowledge on the evolution of physical properties and mixing state of black carbon from sources to the remote atmosphere. We aim to understand how road-to-ambient processing and longer timescale aging in an urban plume affect black carbon physical properties. Refractory black carbon (rBC) was measured during summer 2016 using a Single Particle … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A Soot Particle Aerosol Mass Spectrometer (SP‐AMS) can measure the average coating thickness (coating‐to‐core mass ratio) of BC particle population (Cappa et al., 2012; Wang et al., 2019), while a Single Particle Soot Photometer (SP2) can obtain the coating thickness (coating‐to‐core diameter ratio) of individual BC particles (Krasowsky et al., 2018; S. Liu et al., 2015; Schwarz et al., 2006). Previous studies have used the SP‐AMS and SP2 to investigate the optical effects of core size and coating thickness of BC particles (D. Liu et al., 2017; H. Liu et al., 2020; Unga et al., 2018; Wang et al., 2018; Xie et al., 2020; Zanatta et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A Soot Particle Aerosol Mass Spectrometer (SP‐AMS) can measure the average coating thickness (coating‐to‐core mass ratio) of BC particle population (Cappa et al., 2012; Wang et al., 2019), while a Single Particle Soot Photometer (SP2) can obtain the coating thickness (coating‐to‐core diameter ratio) of individual BC particles (Krasowsky et al., 2018; S. Liu et al., 2015; Schwarz et al., 2006). Previous studies have used the SP‐AMS and SP2 to investigate the optical effects of core size and coating thickness of BC particles (D. Liu et al., 2017; H. Liu et al., 2020; Unga et al., 2018; Wang et al., 2018; Xie et al., 2020; Zanatta et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We compared the number fraction of the thickly coated BC at different measurement sites from literature (Ueda et al, 2016;Schwarz et al, 2008a, b;Wu et al, 2017;Wang et al, 2014Huang et al, 2012;Metcalf et al, 2012;Shiraiwa et al, 2007;McMeeking et al, 2012;Subramanian et al, 2010;Saha et al, 2018;Krasowsky et al, 2018;Holder et al, 2014) and the results are shown in Fig. 3.…”
Section: Mixing States Of the Thinly Coated And Thickly Coated Bc-con...mentioning
confidence: 99%